G (x) = root [3] {x ^ {2} - 1} + 2 sqrt {x + 1}이면 g (3)는 무엇입니까?

G (x) = root [3] {x ^ {2} - 1} + 2 sqrt {x + 1}이면 g (3)는 무엇입니까?
Anonim

대답:

# g (3) = 6 #

설명:

거기에 3을 대체하십시오. #엑스#

# g (3) = 루트 (3) (3 ^ 2-1) + 2sqrt (3 + 1) #

#g (3) = 루트 (3) 8 + 2sqrt4 #

# g (3) = 2 + 2sqrt4 #

# g (3) = 2 + 2xx2 #

# g (3) = 2 + 4 #

# g (3) = 6 #

대답:

# g (3) = 6 #

설명:

플러그 #3# 에 대한 #엑스#

# g (3) = root3 (3 ^ 2-1) + 2sqrt (3 + 1) #

단순화

# g (3) = root3 (9-1) + 2sqrt (4) #

# g (3) = root3 (8) + 2sqrt (4) #

# g (3) = 2 + 2 (2) #

# g (3) = 2 + 4 #

# g (3) = 6 #